2010
DOI: 10.1007/s00586-010-1458-y
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic stabilization with external fixator in a patient with lumbosacral agenesis

Abstract: A case of caudal regression syndrome in which rehabilitation was obtained by lumbopelvic distraction and stabilization with external fixation Orthofix Ò is presented. The objective of the study is to describe the benefit of spine external fixator in caudal regression syndrome. Caudal regression syndrome is a rare and sporadic neural defect of distal spinal segments affecting the development of the spinal cord. It is characterized by vertebropelvic instability and essentially manifests as neurological deficit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…According to the limited number of studies on spinopelvic stability, we found that bone nonunion had a relatively high incidence. [ 5 , 6 , 8 ] Yazici et al reported 3 cases with lumbosacral agenesis that underwent posterior lumbopelvic instrumentation and fixation with autogenic anterior tibial cortical structural graft for laminopelvic bridging and demineralized bone matrix for augmentation of osteoinduction. [ 7 ] Successful fusion was achieved for all 3 patients, which allowed for sitting.…”
Section: Discussionmentioning
confidence: 99%
“…According to the limited number of studies on spinopelvic stability, we found that bone nonunion had a relatively high incidence. [ 5 , 6 , 8 ] Yazici et al reported 3 cases with lumbosacral agenesis that underwent posterior lumbopelvic instrumentation and fixation with autogenic anterior tibial cortical structural graft for laminopelvic bridging and demineralized bone matrix for augmentation of osteoinduction. [ 7 ] Successful fusion was achieved for all 3 patients, which allowed for sitting.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] The main treatment for sacral agenesis is correction of deformities and orthopaedic intervention. [ 14 , 18 , 19 ] Moreover for neurogenic bladder, the current treatment methods include medications, neuromodulation, botulinum toxin A injection, surgical procedures, issue engineering, stem cell transplantation, and gene therapy, besides, Traditional Chinese Medicine such as acupuncture. A review demonstrated that acupuncture could have a beneficial effect on neurological function recovery.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 Only few of them consider quality of life of these patients underlining the importance of stable sitting position without hand support. 5 To achieve this goal, knee and hip joint contractures may require (or not) surgical intervention, depending on the patient. 15 Spino-pelvic instability is another problem causing declined torso position.…”
Section: Discussionmentioning
confidence: 99%
“…4 Currently, absence of a sacrum and partial absence of one or more vertebrae cephalad is classified as caudal regression syndrome. 5 Despite great variety of defects in this syndrome, spinal malformations are always accompanied by anomalies of the viscera, especially of urogenital system. 4,5 It is often associated with neurogenic bladder, which may lead to increased risk of renal impairment caused by recurring urinary tract infections and urinary retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation